Ixazomib, Lenalidomide, and Dexamethasone (IRD) Treatment with Cytogenetic Risk-Based Maintenance in Transplant-Eligible Myeloma: A Phase 2 Multicenter Study by the Nordic Myeloma Study Group - Partanen, Anu (Switzerland, 2025)
Scarce data exist on double maintenance in transplant-eligible high-risk (HR) newly diagnosed multiple myeloma (NDMM) patients. This prospective phase 2 study enrolled 120 transplant-eligible NDMM patients. The treatment consisted of four cycles of ixazomib-lenalidomide-dexamethasone (IRD) induction plus autologous stem cell transplantation followed by IRD consolidation and cytogenetic risk-based maintenance therapy with lenalidomide + ixazomib (IR) for HR patients and lenalidomide (R) alone for NHR patients. The main endpoint of the study was undetectable minimal residual disease (MRD) with sensitivity of <10-5 by flow cytometry at any time, and other endpoints were progression-free survival (PFS) and overall survival (OS). We present the preplanned analysis after the last patient has been two years on maintenance. At any time during protocol treatment, 28% (34/120) had MRD < 10-5 at least once. At two years on maintenance, 66% of the patients in the HR group and 76% in the NHR group were progression-free (p = 0.395) and 36% (43/120) were CR or better, of which 42% (18/43) had undetectable flow MRD <10-5. Altogether 95% of the patients with sustained MRD <10-5, 82% of the patients who turned MRD-positive, and 61% of those with positive MRD had no disease progression at two years on maintenance (p < 0.001). To conclude, prolonged maintenance with all-oral ixazomib plus lenalidomide might improve PFS in HR patients.